Divine Sounds from the Heart-Singing Unfettered in their Own Voices the Bhakti Movement and its Women Saints (12th to 17th Century). - Pande, Rekha (Newcastle upon Tyne : Cambridge Scholars Pub., 2010)
Through the centuries of patriarchal control women have negotiated many layers and levels of existence working out various forms of resistance through various mediums which have often gone unnoticed. Bhakti was one such medium which was open to women. Since religious space was the only space available to women in medieval times many women embraced bhakti and it provided them the space to define their own truths in voices that revision society, polity, relationships and religions. Women's art ...
TABLE OF CONTENTS; PREFACE; ACKNOWLEDGEMENTS; CHAPTER I; CHAPTER II; CHAPTER III; CHAPTER IV; CHAPTER V; CHAPTER VI; CHAPTER VII; CHAPTER VIII; APPENDIX; BIBLIOGRAPHY; INDEX.
Description based on print version record.
Keywords: Bhakti; Women -- Religious life -- India; Women saints -- India; Bhakti; Women saints -- India; Women -- Religious life -- India; RELIGION / Hinduism / General; Electronic books